Almanac : poems - Smith, Austin, 1982- (Princeton series of contemporary poets., 2013)
Almanac is a collection of lyrical and narrative poems that celebrate, and mourn the passing of, the world of the small family farm. But while the poems are all involved in some way with the rural Midwest, particularly with the people and land of the northwestern Illinois dairy farm where Austin Smith was born and raised, they are anything but merely regional. As the poems reflect on farm life, they open out to speak about childhood and death, the loss of tradition, the destruction of the natural world, and the severing of connections between people and the land. This.